The Restorative Justice Effectiveness In Law Enforcement Of Damage Of Goods Crime - Vikha Anief Obaydhillah; Gunarto Gunarto (Universitas Islam Sultan Agung, 2021)
Legal settlement based on restorative justice in the crime of destruction of goods is basically a more effective and efficient solution, however, not all people are willing to carry out this legal effort. This study aims to analyze more deeply the position of restorative justice in law enforcement in cases of destruction of goods. The research approach used is sociological juridical. The results of the analysis in this paper find the fact that the settlement of cases based on restorative justice which is carried out through legal remedies outside the court basically has advantages. The main advantage of resolving cases including criminal cases outside the court with alternative dispute resolution (ADR) is that decisions made by the parties themselves (win win solutions) reflect a sense of justice. However, this has not been effective in resolving cases of vandalism. This is shown by the data above which shows the lack of implementation of alternative dispute resolution in resolving criminal cases of vandalism in the community.